Reference ranges of tricuspid annulus geometry in healthy adults using a dedicated three-dimensional echocardiography software package - Muraru, Denisa; Gavazzoni, Mara; Heilbron, Francesca; Mihalcea, Diana J.; Guta, Andrada C.; Radu, Noela; Muscogiuri, Giuseppe; Tomaselli, Michele; Sironi, Sandro; Parati, Gianfranco; Badano, Luigi P. (Frontiers in Cardiovascular Medicine, 2022)
Background. Tricuspid annulus (TA) sizing is essential for planning percutaneous or surgical tricuspid procedures. According to current guidelines, TA linear dimension should be assessed using two-dimensional echocardiography (2DE). However, TA is a complex three-dimensional (3D) structure. Aim. To identify the reference values for TA geometry and dynamics and its physiological determinants using commercially-available three-dimensional echocardiography (3DE) software package dedicated to tricuspid valve (4D AutoTVQ, GE). Methods. A total of 254 healthy volunteers (113 men, 47±11 years) were evaluated using 2DE and 3DE. TA 3D area, perimeter, diameters, and sphericity index were assessed at mid-systole, early- and end-diastole. Right atrial (RA) and ventricular (RV) end-diastolic and end-systolic volumes were also measured by 3DE. Results. The feasibility of the 3DE analysis of TA was 90%. TA 3D area, perimeter, and diameters were largest at end-diastole and smallest at mid-systole. Reference values of TA at end-diastole were 9.6±2.1cm2 for the area, 11.2±1.2 cm for perimeter, and 38±4 mm, 31±4 mm, 33±4 mm, and 34±5 mm for major, minor, 4-chamber and 2-chamber diameters, respectively. TA end-diastolic sphericity index was 81±11%. All TA parameters were correlated with body surface area (BSA) (r from 0.42 to 0.58, p<0.001). TA 3D area and 4-chamber diameter were significantly larger in men than in women, independent of BSA (p<0.0001). There was no significant relationship of TA metrics with age, except for the TA minor diameter (r = -0.17, p <0.05). When measured by 2DE in 4-chamber (29±5 mm) and RV-focused (30±5 mm) views, both TA diameters resulted significantly smaller than the 4-chamber (33±4 mm; p<0.0001), and the major TA diameters (38±4 mm; p<0.0001) measured by 3DE. At multivariable linear regression analysis, RA maximal volume was independently associated with both TA 3D area at mid-systole (R2=0.511, p<0.0001) and end-diastole (R2=0.506, p<0.0001), whereas BSA (R2=0.526, p<0.0001) was associated only to mid-systolic TA 3D area. Conclusions. Reference values for TA metrics should be sex-specific and indexed to BSA. 2DE underestimates actual 3DE TA dimensions. RA maximum volume was the only independent echocardiographic parameter associated with TA 3D area in healthy subjects.